Radiographic signs of acetabular retroversion using a low-dose slot-scanning radiographic system (EOS®). Issue 3 (August 2019) - Mussmann, B.; Jensen, C.; Bensen, A.S.; Torfing, T.; Ovesen, O.; Overgaard, S.
Abstract: Introduction: Acetabular retroversion is assessed using pelvic X-ray. Cross-over-sign (COS), posterior-wall-sign (PWS) and ischial-spine-sign (ISS) are important radiographic signs of the condition. The pelvic area is sensitive to radiation and thus, possibilities to reduce dose should be considered. The purpose was to compare radiographic signs of acetabular retroversion on conventional pelvic anteroposterior (AP) X-rays with a low-dose slot-scanning system (EOS) in a sample of patients with retroversion of the acetabulum and to compare the radiation doses. Methods: 34 participants with radiographic signs of acetabular retroversion in one or both hips on conventional pelvic X-ray were consecutively recruited. Pelvic EOS-images were acquired in each patient and COS, PWS, ISS, COS-ratio and PWS-ratio was assessed. Radiation dose comparison of X-ray vs. EOS was performed using Dose-Area Products. Results: Retroversion was present in 57 out of 68 hips. The absolute agreement was 91%, 84% and 76% for COS, PWS and ISS, respectively. No statistically significant differences were present between COS-ratio and PWS-ratio in either modality and Bland–Altman limits of agreement were narrow. The mean radiation dose was 1053 mGy*cm 2 in X-ray and 593 mGy*cm 2 in EOS (p = 0.003). Conclusion: The results indicate that pelvic EOS provides diagnostic qualities similar to conventional X-ray using 44% less radiation when radiographic signs of acetabular retroversion are assessed. Highlights: Acetabular retroversion can reliably be assessed using a slot-scanning system. Agreement between slot-scanning and digital radiography is high for radiographic signs of retroversion. Radiation dose can be substantially reduced compared to digital radiography.